On the Growth of Vapour Bubble in Metastable Liquid as Variational Problem - Gvelesiani, Anzor I. (Journals of Georgian Geophysical Society, 2019)
Bubble growing process is considered theoretically when bubble consists saturated vapour of liquid and when we have vapour-gas bubble on the base of generalized Rayleigh-Plesset equation. For this purpose we use variational method with help of which we seek for those cases corresponding Euler-Poisson equations integral curves. Obtained EP- equations allow us to find extremals of our variational task. In conclusion, the Rayleigh-Taylor instability is considered general case of nonspherical perturbances for spherical bubbles and the case of the radial perturbances of bubbles.